Techno-Economic Feasibility Study of Management Palm-Oil Fronds Into Compost and Mulch in West Aceh District - Ramayanti Bulan; Safrizal Safrizal; Muhammad Yasar; Saiful Bahri (Department of Agricultural Engineering, Syiah Kuala University, 2018)
Abstract. The development of palm-oil plantations aims to create employment opportunities, improve the prosperity of community and income country. However, palm-oil plantation waste in the form of fronds has not been optimally managed. The aims of this research is to study of palm-oil fronds management feasibility in palm-oil plantations to be compost and mulch. The goals of this research is to study of palm-oil fronds management feasibility in palm-oil plantations to be compost and mulch. The study was conducted on one of the palm-oil plantations in West Aceh District. The techno-economic feasibility study refers to the use of all the necessary equipment and machinery in the management of palm-oil fronds. Factors to be considered in techno-economic analysis are NPV, Net B/C, IRR, Payback Period and BEP. The palm-oil plantation area studied is 576 ha which has the potential to produce as palm-oil fronds as much as 781 unit/day. Palm-oil fronds management uses two scenarios: centralized management scenarios (designed for only one processing unit) and decentralization (designed into two processing units). The results show that the techno-economic criteria of NPV, Net B/C, IRR, payback period and BEP for scenario one are Rp 766,518,333; 1.25; 25%; 8.09 years; 23,290.72 tons, respectively. The techno-economic criteria of NPV, Net B/C, IRR, payback period and BEP for scenario two are Rp 487,406,792; 1.07; 15%; 14.23 years; 40,935.51 tons, respectively. The value of these techno-economic criteria suggests that the management of palm-oil fronds from centralized scenarios is more feasible to undertake than the decentralization scenario. Studi Kelayakan Tekno-Ekonomi Pengelolaan Pelepah Sawit Menjadi Kompos dan Mulsa di Kabupaten Aceh Barat Abstrak. Pengembangan perkebunan kelapa sawit bertujuan untuk menciptakan kesempatan kerja, meningkatkan kesejahteraan masyarakat dan sektor penghasil devisa negara. Namun, Limbah perkebunan kelapa sawit berupa pelepah sawit belum dikelola secara optimal. Tujuan penelitian ini adalah melakukan kajian kelayakan tekno-ekonomi dari pengelolaan limbah pelepah sawit menjadi kompos dan mulsa. Kajian dilaksanakan pada salah satu perkebunan kelapa sawit di Kabupaten Aceh Barat. Studi kelayakan tekno-ekonomi merujuk pada penggunaan seluruh alat dan mesin yang diperlukan dalam pengelolaan limbah pelepah sawit tersebut. Faktor yang dipertimbangkan diantara adalah NPV, Net B/C, IRR, Payback Period dan BEP. Luas perkebunan yang dikaji adalah 576 ha yang berpotensi menghasilkan pelepah sawit sebanyak 781 pelepah/hari. Potensi limbah pelepah sawit tersebut ditangani dengan dua skenario yaitu skenario pengelolaan sentralisasi (didesain hanya satu unit pengolahan) dan desentralisasi (didesain menjadi dua unit pengolahan). Hasilnya menunjukkan bahwa kriteria tekno-ekonomi NPV, Net B/C, IRR, payback period dan BEP untuk skenario satu masing-masing adalah Rp 766,518,333; 1.25; 25%; 8.09 tahun; 23,290.72 ton. Kriteria tekno-ekonomi NPV, Net B/C, IRR, payback period dan BEP untuk skenario dua masing-masing adalah Rp 487,406,792; 1.07; 15%; 14,23 tahun; 40,935.51 ton. Nilai kriteria tekno-ekonomi ini mengisyaratkan bahwa pengelolaan pelepah sawit skenario sentralisasi lebih layak untuk dilakukan dari pada skenario desentralisasi.